High Gas Adsorption Capacity of an agw‐Type Metal–Organic Framework Decorated with Methyl Groups. Issue 29 (21st September 2016) - Du, Liting; Lu, Zhiyong; Xu, Li; Ma, Mengtao; Zhang, Jinchi
Abstract : A new methyl‐functionalized metal–organic framework, {Cu3 (CMPEIP)2 · 2H2 O} n {m‐NB13, H3 CMPEIP = 5‐[(4‐carboxy‐2‐methylphenyl)ethynyl]isophthalic acid} was solvothermally synthesized and structurally characterized. {Cu3 (CMPEIP)2 · 2H2 O} n exhibits a high BET surface area of 3215.4 m 2  g –1, a large H2 uptake (1.92 wt.‐% at 0.1 MPa and 77 K), and excellent CO2 storage capacity (9.24 wt.‐% at 0.1 MPa and 298 K). Abstract : A new methyl‐functionalized metal–organic framework, {Cu3 (CMPEIP)2 · 2H2 O} n {m‐NB13, H3 CMPEIP = 5‐[(4‐carboxy‐2‐methylphenyl)ethynyl]isophthalic acid} is synthesized and characterized. {Cu3 (CMPEIP)2 · 2H2 O} n exhibits a high BET surface area of 3215.4 m 2  g –1, a large H2 uptake (1.92 wt.‐% at 0.1 MPa and 77 K), and excellent CO2 storage capacity (9.24 wt.‐% at 0.1 MPa and 298 K).